Optimalisasi Pendapatan Asli Daerah (PAD) di Kotamadya Denpasar Menggunakan Sistem Informasi Administrasi Pajak Reklame (SIAP) Berbasis Sistem Informasi Geografis (SIG) - Mahardika, I Wayan Agus Ista Putra; Sukmaaji, Anjik; Taufik, Vicky M (Jurnal JSIKA, 2012)
To managing an advertisement tax, there are several constraints faced in increasing local revenues, especially in Denpasar, is how the Department of Hygiene and Gardening increase their revenue of optimization advertising or publicity from the frauding size of  billboards? Optimization Revenue Program in the municipality of Denpasar Use Tax Administration Information System for Advertisement Based Geographic Information System (GIS). The function of this program is to assist and facilitate the Department of Hygiene and Gardening in the revenue’s optimization, and make easier in optimization of local income tax on billboards. Keyword: optimization, frauding